1995
DOI: 10.1007/bf02211796
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anesthesia in anin vitro fertilization and embryo transfer program

Abstract: Epidural anesthesia is an effective method for transvaginal oocyte retrieval but does not improve the treatment outcome as compared to an intravenous sedation with mask-assisted ventilation using propofol and nitrous oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…36 Epidural anesthesia is another effective option for egg retrieval; however, it does not improve treatment outcomes in comparison to intravenous sedation. 37 Spinal anesthesia has been used as an effective method. Martin et al demonstrated that fentanyl, in addition to lidocaine with spinal anesthesia made patients more comfortable during an egg retrieval procedure than lidocaine alone.…”
Section: Ivf Retrievalmentioning
confidence: 99%
“…36 Epidural anesthesia is another effective option for egg retrieval; however, it does not improve treatment outcomes in comparison to intravenous sedation. 37 Spinal anesthesia has been used as an effective method. Martin et al demonstrated that fentanyl, in addition to lidocaine with spinal anesthesia made patients more comfortable during an egg retrieval procedure than lidocaine alone.…”
Section: Ivf Retrievalmentioning
confidence: 99%
“…Nerve blocks (ovarian block and paracervical block) as an additional method for pain relief proved no harm on the IVF success [ 3 , 4 ]. Epidural anesthesia is not commonly used but it seems a safe alternative choice, as it was not associated with toxic effects [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Women undergoing SA had increased pregnancy rates compared with women who received GA for IVF [ 1 , 2 ]. Epidural anesthesia and sedation (propofol and mask-assisted ventilation with nitrous oxide) had the same outcomes in terms of pregnancy [ 5 ]. No difference was found between performing preovarian block and paracervical local anesthetic block for oocyte retrieval [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to sedation with propofol and mask-assisted ventilation with nitrous oxide, epidural bupivacaine anesthesia resulted in fewer complications, especially nausea and emesis. 54 Spinal anesthesia may be preferable to epidural anesthesia due to the reduced anesthetic failure rate, lower systemic and follicular concentrations of anesthetic agent, and a faster recovery profile. 55 Spinal administration of 1.5% hyperbaric lidocaine (60 mg) is associated with significantly shorter recovery times than spinal administration of 5% hyperbaric lidocaine in patients undergoing ART procedures.…”
Section: Ultrasonographic-guided Transvaginal Oocyte Retrievalmentioning
confidence: 99%